Occupational exposure to trichloroethylene and risk of non-Hodgkin lymphoma and its major subtypes: a pooled IinterLlymph analysis. Issue 11 (23rd July 2013) - Cocco, P; Vermeulen, R; Flore, V; Nonne, T; Campagna, M; Purdue, M; Blair, A; Monnereau, A; Orsi, L; Clavel, J; Becker, N; de Sanjosé, S; et al.
Abstract : Objectives: We evaluated the association between occupational exposure to trichloroethylene (TCE) and risk of non-Hodgkin lymphoma (NHL) in a pooled analysis of four international case-control studies. Methods: Overall, the pooled study population included 3788 NHL cases and 4279 controls. Risk of NHL and its major subtypes associated with TCE exposure was calculated with unconditional logistic regression and polytomous regression analysis, adjusting by age, gender and study. Results: Risk of follicular lymphoma (FL), but not NHL overall or other subtypes, increased by probability (p=0.02) and intensity level (p=0.04), and with the combined analysis of four exposure metrics assumed as independent (p=0.004). After restricting the analysis to the most likely exposed study subjects, risk of NHL overall, FL and chronic lymphocytic leukaemia (CLL) were elevated and increased by duration of exposure (p=0.009, p=0.04 and p=0.01, respectively) and with the combined analysis of duration, frequency and intensity of exposure (p=0.004, p=0.015 and p=0.005, respectively). Although based on small numbers of exposed, risk of all the major NHL subtypes, namely diffuse large B-cell lymphoma, FL and CLL, showed increases in risk ranging 2–3.2-fold in the highest category of exposure intensity. No significant heterogeneity in risk was detected by major NHL subtypes or by study. Conclusions: Our pooled analysis apparently supports the hypothesis of an increase in risk of specific NHL subtypes associated with occupational exposure to TCE.